2020
DOI: 10.1021/acsami.0c12583
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Mechanistic Origins of Photocatalytic Hydrogen Evolution Mediated by MoS2/CdS Quantum-Dot Heterostructures

Abstract: Solar fuel generation mediated by semiconductor heterostructures represents a promising strategy for sustainable energy conversion and storage. The design of semiconductor heterostructures for photocatalytic energy conversion requires the separation of photogenerated charge carriers in real space and their delivery to active catalytic sites at the appropriate overpotentials to initiate redox reactions. Operation of the desired sequence of light harvesting, charge separation, and charge transport events within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 61 publications
3
46
0
Order By: Relevance
“…According to the different energy band arrangements, 2D single-layer semiconductor heterostructures can be divided into type I, type II, and type III. Compared with type I with a staggered band and type III with a broken band, the band of type-II heterostructure is symmetrically staggered. Light-excited electron transitions cause electrons and holes to accumulate on different semiconductor monolayers, thereby achieving the effective separation of electrons and holes. In particular, some recent studies have reported that the experimentally synthesized type-II heterostructure exhibits excellent photocatalytic activity. Tang et al have confirmed that the type-II heterostructure formed by the vertical growth of ZnO 2D nanosheets sensitized by nonmetallic carbon (C) dots helps to improve the charge transfer between C dots and ZnO and enhance the photoanodic performance .…”
mentioning
confidence: 99%
“…According to the different energy band arrangements, 2D single-layer semiconductor heterostructures can be divided into type I, type II, and type III. Compared with type I with a staggered band and type III with a broken band, the band of type-II heterostructure is symmetrically staggered. Light-excited electron transitions cause electrons and holes to accumulate on different semiconductor monolayers, thereby achieving the effective separation of electrons and holes. In particular, some recent studies have reported that the experimentally synthesized type-II heterostructure exhibits excellent photocatalytic activity. Tang et al have confirmed that the type-II heterostructure formed by the vertical growth of ZnO 2D nanosheets sensitized by nonmetallic carbon (C) dots helps to improve the charge transfer between C dots and ZnO and enhance the photoanodic performance .…”
mentioning
confidence: 99%
“…In this respect, hydrogen is considered as a promising candidate for next-generation energy carriers due to its large energy content of ~122 kJ•g −1 and clean emission [221][222][223] . Compared with the environmentally unfriendly steam reforming of natural gas and the expensive electrolysis of water, photocatalytic water splitting is considered to be a promising approach for the production of H2 due to its effective utilization of solar energy 29, [224][225][226][227][228][229][230][231][232][233][234][235] . Since Fujishima and Honda 94 proposed the first photoelectrochemical water splitting system in 1972, photocatalytic water splitting has drawn immense attention and leading-edge achievements emerged in an endless stream to date, and the typical works are concluded in Table 3 114,143,147, 236-240. The basic steps in the process of photocatalytic water splitting on a semiconductor photocatalyst are shown in Fig.…”
Section: Water Splittingmentioning
confidence: 99%
“…Much attention has been given to QDs as ideal luminophores for their wide absorption spectra, controllable emission spectra, and high stability [24–30] . In addition to applications in LSC technology, the controllable emissions spectra of QDs have enabled the development of QDs as a photocatalyst in hydrogen production [31–36] . The color conversion properties of QDs lead to their application in high‐efficiency LEDs [37–43] .…”
Section: Introductionmentioning
confidence: 99%